Does Participation in Global Value Chains Reduce Spatial Inequalities within Countries? - Grover, Arti; Lall, Somik V. (World Bank, Washington, DC, 2021)
This paper examines whether a country’s participation in global value chains supports spatial convergence in the domestic economy. In theory, production disintegration through “unbundling” makes industrial development less lumpy, providing opportunities for smaller cities to plug and play in niche spaces while not having to fight the agglomeration economies offered by large metropolitan areas. Using data on the size distribution of cities within countries and the Organisation for Economic Co-operation and Development’s Trade in Value Added database, the paper finds that integration in global value chains is strongly associated with greater concentration in large urban agglomerations, not less. A unit standard deviation increase in domestic value added in exports of intermediate products is associated with a decline of 0.1 standard deviation in the Zipf coefficient, an index measuring spatial dispersion. Spatial concentration is strongest for global value chains involving knowledge-intensive business services and high-technology manufacturing.